All things new - Austin, Lynn N. (Bethany House, 2012)
In the aftermath of the Civil War, Josephine vows to rebuild her family's once-grand Virginia plantation. But in the face of such destruction, is redemption and faith in God possible? The difficult years of the Reconstruction era are brought to life by interweaving the stories of three women--daughter, mother, and freed slave--in a riveting tale.